(NiSTORIQ I LINGWISTIKA (B/s - (NpRON[TEJN(B, (NaLEKSANDR pAWLOWI^ s; (NkOWALENKO(B, (N`RIJ wASILXEWI^ s; (NwWEDENSKAQ(B, (Nl@DMILA aLEKSEEWNAs ((NrOSTOW(B-(NNA(B-(NdONU (B:s (NiZD(B-(NWO rOSTOW(B. (NUN(B-(NTA(B,s, 1970)
(NkOMMENTARII I IMENNOJ UKAZATELX(B: (NS(B. 343 - 365s
Keywords: (NlINGWISTIKAs; (NqZYKOZNANIEs